EFFECT OF ZEOLITE AND CHICKEN MANURE ON NUTRIENT RESIDUE IN THE SOIL - Lenny M. Estiaty; Suwardi Suwardi; Ika Maruya; Dewi Fatimah (Institut Teknologi Bandung, 2006)
Fertilizer is one of nutrient sources that very important for increasing agricultural production besides improvement of soil properties by application of soil amendments such as zeolites and compost. Addition of zeolites increase the cation exchange capacity (CEC) and fertilizer effeciency while compost used as source organic matter and nutrients in the soil. Estiaty (2005) showed that application of 20 ton/ha zeolite and chicken manure compost 10 ton/ha with basal fertilizers of N, P, K 200 kg/ha respectively is the best dosage for Ipomoea reptans. From the second period showed that there was higher nutrient residue in the soil applied by zeolite and chicken manure compost. These facts were shown from better plant growth and production in the soil applied by zeolite in the second period. The objective of this experiment is to calculate the residue of nutrients from the application of zeolite and chicken manure in the first planting before. The experiment was conducted by application of N, P, and K fertilizers in different rates in the soils after using first planting with zeolite and chicken manure. Ipomoea reptans was used as indicator plant. Experiment was conducted in two stages; first planting such as Estiaty (2005) treatments following by second planting with N, P, K in different dosages. This experiment was conducted in green house of Cikabayan, IPB Darmaga Campus while soil and plant analysis was conducted in the laboratory of Department of Soil Science and Land Management. The result showed that zeolite and chicken manure increase the efficiency of N, P, K fertilizers in the second planting. In the second planting of Ipomoea reptans, the need of N, P, K fertilizers were only half of the first planting with the production of nearly the same. Application of zeolite and chicken manure was not only increase the efficiency of N but also increase the available of P and K in the soil.